Computational mesomechanics of titanium surface-hardened by ultrasonic treatment; Physical Mesomechanics; Vol. 20, iss. 3 - Balokhonov R. R. Ruslan Revovich; Romanova V. A. Varvara Aleksandrovna; Panin A. V. Alexey Viktorovich; Kazachenok M. S. Marina Sergeevna (2017, 2017)
Title screen